Implementasi Internalisasi Nilai Disiplin Pada Kegiatan Keagamaan Siswa MI Di Kota Tegal - Dwi Wahyu Aliyyani; Tity Kusrina; Basukiyatno (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to describe the implementation of discipline value internalization in religious activities of students at MI Assalafiyah, Tegal City, to identify its supporting and inhibiting factors, and to analyze its impact on students’ character formation. A qualitative approach with a descriptive method was employed. Data were collected through observation, in-depth interviews with teachers, students, and parents, as well as documentation of religious activities. The findings reveal that the internalization of discipline values is carried out through structured religious practices such as shalat dhuha, tadarus (Qur’an recitation), sholawatan, and the study of the Aqidatul Awwam text. Discipline is instilled through habituation, teacher role modeling, assigning responsibilities to students, and parental support. The main supporting factors include the consistency of activity schedules, teachers’ exemplary roles, and active family involvement. Meanwhile, inhibiting factors consist of differences in students’ maturity levels, fatigue from routines, and the suboptimal internal awareness of discipline among students. The implementation has shown positive impacts on students’ character formation, particularly in time discipline, responsibility, independence, courtesy, and behavioral consistency both at school and at home. This study highlights that religious activities integrated into school life can serve as an effective medium for instilling character values, especially discipline, in a holistic and sustainable manner.